Acute gastric distension caused by superior mesenteric artery syndrome in a bulimic patient - Merino Pasco, Alfonso (2021)
Acute gastric dilation is based on two theories, the mechanical one that is explained by the superior mesenteric artery syndrome and the atonic one; The latter is the product of a medical condition in which the stomach progressively becomes hypotonic and over-distended even in the absence of an obstructive mechanical cause; it most often occurs in patients with eating disorders; which can lead to a rare but fatal complication such as gastric perforation; We present the case of an 18-year-old patient who comes to the emergency service of our hospital with acute abdominal pain, undergoes surgery, where there is perforation of the anterior gastric wall, and a proximal partial gastrectomy is performed, and a sends the specimen for pathology study. Histopathology shows transmural necrosis predominantly in the gastric fundus.